Biblical Bestiary: Camel - Dospěl, Marek (The Biblical archaeology review, 2024)
For millennia, the camel has been an indispensable companion for various peoples throughout the lands of the Bible. Historically, the region has been home to the one-humped Arabian camel, or dromedary (Camelus dromedarius), although the two-humped Bactrian camel (Camelus bactrianus), native to central Asia, also occasionally appears in ancient art and literature. The lucrative trade […]